Larvicidal and pupicidal activities of Foeniculum vulgare essential oil, trans‐anethole and fenchone against house fly Musca domestica and their inhibitory effect on acetylcholinestrase. Issue 11 (3rd November 2021) - Abdel‐Baki, Abdel‐Azeem S.; Aboelhadid, Shawky M.; Sokmen, Atalay; Al‐Quraishy, Saleh; Hassan, Ahmed O.; Kamel, Asmaa A.
Abstract: The present study was designed to evaluate the insecticidal activity of different concentrations of Foeniculum vulgare and two of its components, trans‐anethole and fenchone, against the different stages of Musca domestica . The tested concentrations were applied through a residual film method and topical application on larvae and pupae respectively. Trans‐anethole achieved the best results against larvae when compared with those of the fennel or fenchone with LC50 values of 0.58%, 1.57%, and 17.22%, respectively. Moreover, tans‐anethole killed 100% of larvae at concentration of 2.5% and fennel achieved the same effect at concentration of 10%, meanwhile fenchone did not reach such an effect at any of the tested concentrations. At the concentration of 10%, fennel oil and trans‐anethole induced morphological deformation in the dead larvae such as shrunk bodies with dark colored integument. Regarding the pupicidal activity, fennel oil showed percentage inhibition rate (PIR) of 100% at the concentration of 10% while the same effect was achieved by trans‐anethole at concentration of 5%. On the contrary, fenchone did not show any pupicidal activity. Treatment of the third instar house fly larvae with LC5o of fennel oil, trans‐anethole, and fenchone significantly inhibited the acetylcholinestrase (AchE) when compared with the control untreated larvae. Additionally, the glutathione‐s‐transferase (GST) and malondialdehyde (MDA) production significantly increased in the larvae treated with trans‐anethole. The results of the present study indicate that the insecticidal activity of fennel oil was mainly attributed to the presence of trans‐anethole as a major constituent.